Development of the educational system: European vector – 2025 - Коробчук, Людмила Іванівна; Чайкін, Олександр Валентинович; Морозов, Олег Вікторович; Онищенко, Сергій Вікторович; Вдовиченко, Вікторія Антонівна; Маленюк, Тетяна Володимирівна; Вілкова, Софія Юріївна; Воробйова, Олена Михайлівна; Федорова, Катерина Юріївна; Рожко, Олена Костянтинівна (DEL c.z., 2025)
The collection includes materials of the VI International research and practical internet conference "Development of the educational system: European vector". The materials of the collection will be useful for researchers, scientists, graduate students, researchers, teachers, students.